2012
DOI: 10.1021/jp300837f
|View full text |Cite
|
Sign up to set email alerts
|

XMCD Proof of Ferromagnetic Behavior in ZnO Nanoparticles

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…Moreover, theoretical calculations have suggested that the FM can be induced by cation vacancies in TiO 2 , ZnO, and SnO 2 [9][10][11][12], or by anion vacancies in CeO 2 [13]. Room temperature FM has also been found in metal oxides such as TiO 2 , ZnO, CeO 2 , and SnO 2 which is due to oxygen vacancies and quantum confinement effects according to the experimental results [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, theoretical calculations have suggested that the FM can be induced by cation vacancies in TiO 2 , ZnO, and SnO 2 [9][10][11][12], or by anion vacancies in CeO 2 [13]. Room temperature FM has also been found in metal oxides such as TiO 2 , ZnO, CeO 2 , and SnO 2 which is due to oxygen vacancies and quantum confinement effects according to the experimental results [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 93%
“…[14][15][16][17][18][19][20] In terms of mechanism, alternation of the electronic configuration, which is often a consequence of either intentional or unintentional structural/chemical inhomogeneity introduced in sample synthesis, has been proven as a viable approach to induce ferromagnetism. [21][22][23] In particular, Coey et al proposed that shallow donor electrons can form spin-split impurity bands and bound magnetic polarons. 24 However, the main challenge remains regarding how to harness the oxide nanostructures to produce an enhanced and reliable magnetism in order to become relevant to practical spintronic devices.…”
mentioning
confidence: 99%
“…Recently, engineering the ZnO surface has played important roles in modulating the spin polarization and magnetic order in several material systems including ZnO nanostructures with organic molecule-passivation. [21][22][23]25,29 In fact, Zn K-edge X-ray magnetic circular dichroism measurements revealed a ferromagnetic-like contribution from the interface formed between the ZnO nanoparticle core and the organic molecules. 23 Similarly, spontaneous magnetization and hysteresis were observed in ZnO nanowires (NWs) modified with thiol-capped Ag nanoclusters 30 and in ZnO/ZnS core-shell nanoparticles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[94][95][96] Chaboy et al studied ZnO nanoparticles capped with different molecules using XMCD spectroscopy. 95,96) Figure 10 shows the XMCD results at the Zn L 2;3 and Zn K edges.…”
Section: Zno Nanoparticlesmentioning
confidence: 99%